ASSESSING STUDENTS’ UNDERSTANDING OF PRE-CALCULUS CONCEPTS - Sharma, Jyoti (International Journal of Research -GRANTHAALAYAH, 2017)
Calculus is one of the most momentous achievements of the human intellect (Boyer, 1949). It has given a new direction to the work of mathematicians and scientists. Calculus has exponentially expanded the scope and use of mathematics in other fields. Learning calculus is important to pursue career in applied mathematics.